Updates Therapy for Covid-19 Patients in Pregnant and Lactating Women Review Journal - Liziyyannida Liziyyannida; Suharjono Suharjono (Universitas Malahayati Lampung, 2023)
ABSTRACT Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus that causes the coronavirus disease 2019 (Covid-19). On January 30, 2020 WHO declared Covid-19 a Public Health Emergency of international concern, and caused millions of deaths worldwide. COVID-19 infection can increase in patients who are pregnant. Changes in the immune system and physiology in pregnant women can increase the risk of complications from COVID-19 infection. Pregnancy can compromise the immune system and potentially SARS-CoV-2 infection can increase the risk of pneumonia in pregnant women compared to non-pregnant women. Pregnant women are often excluded from trials because of the risk of toxicity or side effects, resulting in a lack of knowledge about drug use and care during pregnancy. Great uncertainty in therapy due to lack of appropriate treatment information along with the increasing development of changes to the covid19 therapy guidelines. this review aims to gather existing knowledge on currently available drug treatments for COVID-19 in pregnant and lactating women, and produce an analysis of drugs with acceptable safety profiles in the treatment of pregnant and lactating women with COVID-19. This article series uses Mendeley, Google Scholar, ScienceDirect, and PubMed from the NCBI database during October - December 2022. Variables associated with the incidence of under-five malnutrition were maternal nutrition knowledge (p= 0,000; OR = 17,000), parenting and feeding patterns (p= 0,003; OR = 13,500), and family income (p= 0,002; OR = 12,000), while the availability of clean water (p= 0.449; OR = 2.429) was found unrelated with the incidence of under-five malnutrition. In conclusion, the availability of clean water is not related to the incidence of under-five malnutrition, while the other three variables studied are related. So, to prevent under-five malnutrition, it is necessary for mothers to take active action in seeking information on nutritious food, cultivating local food to increase family income and food supply and keep water clean. Further research needs to develop other variables that were not examined by researchers, namely food availability in the family and history of low birth weight babies. Researchers hope that mothers are active in seeking information about nutritious foods, utilizing existing local food to increase family income and food supply so that they are able to serve healthy nutritious food to families, especially toddlers. In addition, keep the water clean by treating drinking water properly so that it does not become a source of spreading disease Keywords: Toddlers, Malnutrition, Income, Knowledge of Nutrition, Parenting ABSTRAK Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) merupakan virus yang berperan atas penyakit coronavirus 2019 (Covid-19). Pada tanggal 30 Januari 2020 WHO menetapkan Covid-19 sebagai Public Health Emergency yang menjadi perhatian Internasional, dan menyebabkan jutaan kematian di seluruh dunia. Infeksi COVID-19 dapat meningkat pada pasien dengan kondisi hamil. Perubahan sistem imun dan fisiologi pada wanita hamil dapat meningkatkan risiko komplikasi infeksi COVID-19. Kehamilan dapat membahayakan sistem kekebalan tubuh dan berpotensi infeksi SARS-CoV-2 dapat meningkatkan risiko pneumonia pada wanita hamil dibandingkan dengan wanita yang tidak hamil. Wanita hamil sering dikeluarkan dari uji coba karena terdapat risiko toksisitas atau efek samping, yang mengakibatkan kurangnya pengetahuan tentang penggunaan obat dan perawatan selama kehamilan. Ketidakpastian terapi yang besar karena kurangnya informasi pengobatan yang tepat seiring dengan meningkatknya perkembangan perubahan pedoman terapi covid19. Kajian ini bertujuan untuk mengumpulkan pengetahuan yang ada tentang perawatan obat yang tersedia saat ini untuk COVID-19 pada wanita hamil dan menyusui, dan menghasilkan analisis obat-obatan dengan profil keamanan yang dapat diterima dalam pengobatan wanita hamil dan menyusui dengan COVID-19. Suran artikel ini menggunakan Mendeley, Google Scholar, ScienceDirect, dan PubMed dari database NCBI selama Oktober - Desember 2022. A search for this article using Mendeley, Google Scholar, ScienceDirect, and PubMed from the NCBI database during October - December 2022 Administration of drugs to pregnant and nursing patients who are exposed to COVID-19 must be seriously considered. Some therapies are not recommended because they can harm the fetus. Safe therapy given to pregnant and lactating patients who are exposed to COVID 19, namely vitamin c, vitamin d, paracetamol, nac, azithromycin, ramdesivir, dexamethasone, enoxaparine, UFH, and vaccines require special attention and close monitoring. Every pregnant woman has the right to have a safe and positive birth experience, including if they are confirmed to have contracted COVID 19 or not. Pregnant women are more susceptible to a number of infectious diseases, including Covid-19. Pregnant women infected with Covid-19 are more at risk of experiencing high levels of severity, requiring ventilators or intensive care. In addition, pregnant women are more susceptible to Covid-19 infection because their pregnancy puts the body in a state of immunosuppression. Immunosuppression is a state of reduced capacity of the immune system. So that the risk of complications increases such as pre-eclampsia, coagulopathy, preterm labor (increased premature birth), miscarriage (neonatal mortality) to death. Given the importance of reducing the risk of COVID-19 for pregnant and lactating women and their neonates, it is important to determine the safety profile of all drugs in real time. So that it can provide accurate data expectations according to the expectations of all pregnant and lactating women in the world. The following types of treatments are presented as safe during pregnancy and lactation, without teratogenic effects and minimal exposure to breastfed infants, namely Azithromycin, Ramdesivir, Dexamethasone, Enoxaparine, and UFH require special attention and close monitoring. As well as additional therapy according to symptoms that arise in pregnant and lactating female patients with COVID-19, namely Vitamin C, Vitamin D, Paracetamol, and NAC. Regarding vaccination, it is strongly recommended that all pregnant women in their second and third trimesters receive the COVID-19 vaccine. The administration of the first dose of vaccination begins in the second trimester of pregnancy and the administration of the second dose is carried out according to the interval of the type of vaccine. The COVID-19 vaccine (either mRNA or viral vector) does not contain replicating virus, so it is highly recommended for pregnant and lactating women with a high risk of exposure. coronavirus continues to undergo COVID-19 vaccination. Keywords: SARS-CoV-2, COVID-19, Pregnant Women, Lactating Woman, Pharmacological Treatment